The Urgency of Supervision on the Performance of PAUD Al Muttaqin Plus Gempol Pasuruan - Mufidah Asfiati; Nurdyansyah Nurdyansyah; Akhtim Wahyuni (Proceedings of The ICECRS, 2020)
Suprvision isa series ofsupervisory activities carried out by a supervisor or headmaster on teacher performance, supervision activities at PAUD level have been regulated in Permendikbud No. 137 of 2014 concerning National Standards for PAUD implementation,but inreality not all PAUD institutions carry out supervision activities according to government policy,so the purpose of this study was to determine the urgency of supervision to improve theacher performance in Al Muttaqin Plus PAUD. This study uses descriptive qualitative methods with participatory observation data collection techniques. And data analysis techniques using data reduction. Based on results and discussion in this study, it was found that the supervision activities carried out by the school principal hada positive impact on the performance of PAUD Al Muttaqin Plus teachers.